Penetapan Konsep Adil Dalam Berpoligami Menurut Hukum Islam dan Hukum Adat - Nur Ainah; Legawan Isa; Bitoh Purnomo (Muqaranah, 2022)
Abstract: This article aims to understand the concept of fairness in polygamy in terms of customary law in Bangun Sari Village, Tanjung Lago District and in terms of Islamic law. This research was motivated by a controversial issue whose debate gave birth to various opinions, especially on the concept of justice as the main requirement in polygamy. In Islamic law and positive law there is no prohibition against polygamy. However, it must go through rules or procedures and applicable legal rules as well as with reasons that can be used as arguments for polygamy. The approach method in this writing is to use a comparative approach. Data was collected by means of interviews and documentation. Data were analyzed descriptively qualitatively. The results of this study state that the application of the concept of fairness in polygamy according to customary law in Bangun Sari Village, Tanjung Lago District is different from Islamic law, namely that polygamy is allowed by traditional leaders who do not have male offspring. The practice of polygamy in Bangun Sari Village, Tanjung Lago District was concluded not to be in accordance with Islamic law.